ASSESSING STUDENT’S WRITING SKILL BY USING GRAPHS: A CASE AT THE SECOND SEMESTER OF ECONOMICS AND BUSINESS FACULTY STUDENTS, UNISBANK SEMARANG - Sarah Sumponogati (Universitas Stikubank (UNISBANK) Semarang, 2018)
The purpose of this study is to determine the effectiveness of the use of graphs for assessing writing for the studenst of the second semester of economics and business faculty, Unisbank Semarang. The method of this study is a mixed method inasmuch as the data were analyzed both in quantitative and qualitative method. The participants are ten students of the second semester of economics and business faculty, Unisbank Semarang. It reveals that the use of graphs can be effective to improve writing skill. However, the biggest obstacle was found when using this kind of method. That is why it is also important to take a look at the students’ background of knowledge because each student has their own characteristics and ability. Keywords: assessing writing, graphs, paragraph.